Kepemimpinan Kepala Sekolah dalam Menerapkan Manajemen Berbasis Sekolah di Sekolah Dasar Islam (SdI) Hidayatul Muhsinin Desa Pal IX Tahun Pelajaran 2019/2020 - Pandi, Abdul (IBTIDA’, 2020)
The researcher is interested to conduct this in order to know: Leadership of the principal in implementing school-based management at SDI. Hidayatul Muhsinin Academic Year 2019/2020. The research problem of this research was: How are the planning, organizing, directing, monitoring and the results of the implementation of School-Based Management at SDI. Hidayatul Muhsinin for the 2019/2020 academic year? The method used in this research was descriptive method with a qualitative approach. The main data sources in this research were principals and teachers obtained through interviews, observation, and documentation. The results of this research indicated that 1) MBS planning at SDI. Hidayatul Muhsinin shows that before making plans, they seek a SWOT analysis first, there are threats, opportunities and know what the advantages and disadvantages of this school condition are.2) MBSOrganizing at SDI. Hidayatul Muhsinin; here we collected human resources and other resources because every school must have a school organization that has certain parts and has their respective duties to carry out these tasks to achieve each mutually agreed goal.3) MBS briefing at SDI. Hidayatul Muhsinin was the principal giving direction and motivating school academy members towards learning goals, including creating a climate that supports them in carrying out their professional work as school principals at SDI. Hidayatul Muhsinin 4) Supervision of MBS at SDI. Hidayatul Muhsinin was the principal conducted supervision continuouslyand guarantees educational activities in schools to achieve their goals, including controlling activities to fit the plan5) The result of implementing MBS at SDI. Hidayatul Muhsinin was that the implementation of school-based management at SDI. Hidayatul Muhsinin was good, because one of the efforts of the principal was to activate or manage all the facilities in this school.